Search for a heavy composite Majorana neutrino in the final state with two leptons and two quarks at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier, 2018)
A search for physics beyond the standard model in the final state with two same-flavour leptons (electrons or muons) and two quarks produced in proton–proton collisions at √s = 13 TeV is presented. The data were recorded by the CMS experiment at the CERN LHC and correspond to an integrated luminosity of 2.3 fb−1. The observed data are in good agreement with the standard model background prediction. The results of the measurement are interpreted in the framework of a recently proposed model in which a heavy Majorana neutrino, N, stems from a composite-fermion scenario. Exclusion limits are set for the first time on the mass of the heavy composite Majorana neutrino, mN , and the compositeness scale . For the case mN = , the existence of Ne (Nμ) is excluded for masses up to 4.60 (4.70) TeV at 95% confidence level.